استخدام استراتيجية تعلم اللغة العربية لدى الطلبة في كلية السلطان إسماعيل بترا الإسلامية العالمية - Mat Nafi, Linamalini; Mat Teh, Kamarul Shukri (RABBANICA - Journal of Revealed Knowledge, 2021)
Several previous studies have shown the weaknesses in mastery of the Arabic language among students in Malaysia. Perhaps the lack of knowledge in language learning strategy and weakness in its use are factors of this problem. This research aims to examine the use of language learning strategy for students when learning Arabic. It also aims to reveal the relationship between the use of a language learning strategy and language achievement and to identify the factors that contribute to its use. This research is a quantitative study through a review. This was accomplished by distributing a questionnaire containing a list of the second language learning strategy 7.0 from an Oxford model on the sample and the Arabic language achievement test. The research sample is 100 students from Sultan Ismail Petra International Islamic College in the state of Kelantan. The research results show that the subjects use the strategy at a moderate level. It also shows that the most common strategies among respondents are metaphysical strategies, and the least used strategies are remembering strategies. The t-test analysis indicated that there is a significant difference in the use of a language learning strategy based on gender. There is also a big difference in using the language learning strategy based on the duration of Arabic language learning outside the classroom per week. Perhaps the results of the research contribute to the theoretical and pedagogical effects especially in the process of teaching and learning the Arabic language in Malaysia.